PMBok Knowledge Areas: Case Study of Project and Stakeholder Management Fail Lessons Learned - Zamri, Masturina Balqiz; Dahri, Nurul Atiqah; Jaafar, Nurul Amisya Nabila; Abdul Rahman, Dina Safiah; Haizal, Mohamad Khairul Haziq; Ismail, Nurul Fatin Athirah; Halim, Siti Noormashetah; James, Stephen Raj; Nur Liyana Sulaiman, (Applied Information Technology And Computer Science, 2023)
Project management within the United States Department of Defense (DOD) is a complex process, requiring meticulous planning and execution. This paper addresses a gap in existing research by employing stakeholder theory and strategic management principles to analyze the DOD Lighter Amphibian Heavy-Lift (LAMP-H) project. The study reveals challenges in stakeholder management, emphasizing the need for a Project Stakeholder Management (PSM) strategy. The paper systematically examines issues in project management, including project manager challenges, integration management, quality management, communication management, and stakeholder management. The case study of the LAMP-H project highlights the consequences of inadequate stakeholder management, strategic inflexibility, and poor project integration. Lessons from the project underscore the importance of comprehensive planning and a focus on quality over quantity in project specifications. The role of project sponsors in stakeholder alignment is emphasised, along with the need for strategic flexibility to adapt to changing project conditions. The paper concludes with recommendations for effective stakeholder management, improved project planning, strategic flexibility, integration management, quality-focused methodologies, and conflict resolution mechanisms to enhance the success of DOD projects.